The Nineteenth Amendment women's right to vote - Peterson, Judy Monroe (Springfield, NJ Enslow Publishers, 1998)
Traces the history of the women's rights movement in the United States which culminated in 1920 with the passage of the constitutional amendment giving women the right to vote.
Keywords: United States. -- History -- Juvenile literature; United States. -- History; Women -- Suffrage -- United States -- History -- Juvenile literature; Constitutional amendments -- United States; Women -- Suffrage -- History; Constitutional amendments -- United States